2009
DOI: 10.1186/1756-9966-28-143
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor in children with neuroblastoma: a retrospective analysis

Abstract: BackgroundDespite aggressive therapy, advanced stage neuroblastoma patients have poor survival rates. Although angiogenesis correlates with advanced tumour stage and plays an important role in determining the tumour response to treatment in general, clinical data are still insufficient, and more clinical evaluations are needed to draw conclusions. The aim of this study was to evaluate vascular endothelial growth factor (VEGF) expression in patients with neuroblastoma, determine whether it correlates with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…VEGF-A, a growth factor for tumour angiogenesis, plays an important role in highly vascularised neuroblastoma tumours (23) and has been chosen as a target for siRNAbased therapeutics. Anti-GD2-DDAB-liposomes loaded with siRNA specific for VEGF-A successfully reduced expression of this gene in neuroblastoma cell lines by 30%, supporting our strategy of using anti-GD2-liposomes as potential carriers for the specific delivery of siRNA to neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF-A, a growth factor for tumour angiogenesis, plays an important role in highly vascularised neuroblastoma tumours (23) and has been chosen as a target for siRNAbased therapeutics. Anti-GD2-DDAB-liposomes loaded with siRNA specific for VEGF-A successfully reduced expression of this gene in neuroblastoma cell lines by 30%, supporting our strategy of using anti-GD2-liposomes as potential carriers for the specific delivery of siRNA to neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…This molecule is well known as a pro-angiogenic factor which stimulates growth of new blood vessels in the tumour and therefore promotes the development of the tumour mass (22). Recent data showed its relevance in neuroblastoma progression (23). Anti-GD2-DDAB-liposomes were chosen as delivery particles for VEGF-A siRNA, because they showed higher siRNA encapsulation efficiencies compared to HSPC-liposomes (Table I).…”
Section: Effects Of Vegf-a Sirna Delivered By Anti-gd2-liposomes In Kmentioning
confidence: 99%
“…Previous studies have shown that high-risk NB with advanced-stage is resistant to various therapeutic approaches resulting in poor survival rates (Ishola and Chung, 2007;Jakovljevic et al, 2009, Cheung, 2012. Therefore, finding new molecular markers in NB is essential to improve targeted therapy via appropriate approach and to increase the survival rates of children.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of EP2 receptor can induce a myriad of tumor-promoting cytokines, chemokines, growth factors, and responding receptors, thereby amplifying inflammation, strengthening the tumor microenvironment, and promoting the growth of tumors in skin, colon, prostate, and brain (14,16,(21)(22)(23)(24). We next examined the expression relationships between EP2 receptor and a number of well-known tumor-associated factors via analyzing the Versteeg-88 dataset ( Table 2) (43), TGF-β1/TGFBR1 (44,45), and VEGF/VEGFR (46). Conversely, none of currently known anti-neuroblastoma factors (0 out of 5), including CSF-2, IFN-γ, IL-2, IL-27, and TNF-α (34,47,48), correlated with EP2 receptor in neuroblastoma tumors (P = 0.001) ( Table 2).…”
Section: Ep2 Receptor Signaling Correlates With Neuroblastoma-promotimentioning
confidence: 99%